2021
DOI: 10.1175/jcli-d-19-0834.1
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Characteristics of Early Autumn Arctic Sea Ice Variability and Its Impact on Winter Eurasian Climate

Abstract: The present study investigated dominant characteristics of autumn Arctic sea ice concentration (SIC) interannual variations and impacts of September–October (SO) mean SIC anomalies in the East Siberian–Chukchi–Beaufort (EsCB) Seas on winter Eurasian climate variability. Results showed that the decreased SO EsCB sea ice is favorable for tropospheric warming and positive geopotential height anomaly over the Arctic region one month later through transporting much more heat flux to the atmosphere from the open wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…In addition to the abovementioned factors, many recent studies have reported that changes in Arctic sea ice in the preceding autumn could influence the Eurasian climate in the following winter. 77,78 Wu et al 77 showed that the intensity of the Siberia high in winter is negatively correlated with the sea ice concentration in the Eastern Arctic Ocean and Siberian marginal seas in the previous autumn. A decrease in the Arctic sea ice concentration is associated with an intensified Siberian high, which may further cause negative temperature anomalies in the mid-to-high latitudes of Eurasia and East Asia.…”
Section: Roles Of Arctic Sea Ice On the Variation Of Eawmmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the abovementioned factors, many recent studies have reported that changes in Arctic sea ice in the preceding autumn could influence the Eurasian climate in the following winter. 77,78 Wu et al 77 showed that the intensity of the Siberia high in winter is negatively correlated with the sea ice concentration in the Eastern Arctic Ocean and Siberian marginal seas in the previous autumn. A decrease in the Arctic sea ice concentration is associated with an intensified Siberian high, which may further cause negative temperature anomalies in the mid-to-high latitudes of Eurasia and East Asia.…”
Section: Roles Of Arctic Sea Ice On the Variation Of Eawmmentioning
confidence: 99%
“…A decrease in the Arctic sea ice concentration is associated with an intensified Siberian high, which may further cause negative temperature anomalies in the mid-to-high latitudes of Eurasia and East Asia. Ding et al 78 have demonstrated that a decrease in sea ice concentration in the East Siberian Chukchi-Beaufort Seas in early autumn (September-October) is associated with negative surface temperature anomalies in northeastern China in the following late winter (January-March).…”
Section: Roles Of Arctic Sea Ice On the Variation Of Eawmmentioning
confidence: 99%
“…As a component of the Earth's climate system, Arctic sea ice plays an important role in the surface energy budget of the high latitudes in the Northern Hemisphere by regulating the surface albedo and the turbulent heat and momentum fluxes at the ocean-atmosphere interface. The atmospheric response to reductions in Arctic sea ice is often associated with changes in the AO [31,32]. Figure 5 shows the composite Arctic sea ice anomalies in the negative and positive AO phases.…”
Section: Causes For the Different Predictabilitymentioning
confidence: 99%
“…Sudden stratospheric warming (SSW) can dramatically weaken the stratospheric polar vortex, and the weakened Northern Hemispheric stratospheric polar vortex is beneficial for the turning of the tropospheric and near-surface AO to the negative phase in winter [29,30]. In addition, the recent accelerated reduction in Arctic sea ice is also considered to be a possible factor in the changes in the midhigh latitude circulation in winter, and the response characteristics of circulation are often similar to AO modes, especially in some numerical models [31,32]. However, the relatively short observational record and the low mid-latitude signal-to-noise ratio (SNR) lead to difficulties when explaining the physical connection between Arctic sea ice and the AO mode, so this connection is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous studies have tended to focus on seaice change in the winter season or year-round and on interannual timescales, with limited attention having been paid to autumn and interdecadal timescales. Although recent studies argued there is diverse Eurasian temperature and precipitation responses to BKL sea-ice loss in autumn (Li and Wang, 2012;Ding et al, 2020;Zhang and Screen, 2021), their focus was on the interannual rather than interdecadal timescale. Chen and Wu (2018) and Ding and Wu (2021) explored how autumn EsCB sea-ice loss can influence spring Eurasian temperature.…”
Section: Introductionmentioning
confidence: 99%